The Effectiveness of Rosemary and Mefenamic Acid Capsules on the Quality of Life of Students with Primary Dysmenorrhea - Fahimeh Tahoonian Golkhatmy; Zahra Abedian; Ahmad Emami; Habibollah Esmaily (Mashhad University of Medical Sciences, 2024)
Background & aim: Dysmenorrhea is one of the main factors affecting the quality of life.  This study aimed to determine the impact of rosemary and mefenamic acid capsules on the quality of life of students with primary dysmenorrhea.Methods: This double-blind clinical trial study was performed on 82 students with primary dysmenorrhea from June to september 2018 at the Faculty of Medicine of the Islamic Azad University of Mashhad. Students with moderate dysmenorrhea, after controlling two menstrual cycles by the convenience sampling method and using PASS software, were randomly assigned to the rosemary and mefenamic acid groups using double blocks. They consumed rosemary and mefenamic acid capsules every 8 hours for the first 3 days of intervention cycles. The SF-36 questionnaire was used to assess quality of life before and after the intervention at the end of menstrual bleeding.  The data were analyzed using SPSS 24 and descriptive and interpretive statistical tests.Results: The mean score of physical health in the first cycle after the intervention increased by 300.07±62.43 and 306.00±66.11and in the second cycle after the intervention increased by 306.54±63.90and 308.63±64.14 (P=0.94). The mean score of mental health in the first cycle after the intervention increased by283.90±58.48 and 282.98±65.63 and in the second cycle after the intervention increased by 261.13 ±80.61and 258.94± 86.67 (P=0.90).Conclusion: Consumption of rosemary and mefenamic acid capsules improves the quality of life by increasing the scores of physical and mental health.